Legal Protection and Settlement of Electronic Buying and Selling Transaction Disputes Regarding Goods Not Conforming to Orders - Myranika, Annie (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
AbstractOnline buying and selling transactions, which are a development of buying and selling activities, are a form of binding agreement for both parties, but are carried out using internet facilities and are carried out without any direct interaction from both parties. This research aims to examine and analyze the law regarding a problem in society regarding online buying and selling transactions that result in goods not being ordered. The research method used in this research is a qualitative juridical method in which an existing problem is analyzed using legal source materials. The results and conclusions in this research are that the development of e-commerce in Indonesia is regulated in Law no. 11 of 2008 concerning Information and Electronic Transactions, and Law Number. 8 of 1999 concerning Consumer Protection regulates consumer protection, and forms of resolution of problems regarding online buying and selling can be resolved through court or outside court such as mediation and arbitration.Keywords: Legal Protection; Dispute Resolution; Online Buying and Selling; Inappropriate Items